Competing coalitions in international monetary policy games - Marion Kohler (Hamburg Institute of International Economics (HWWA), 2004)
In Kohler (2002) we analyse coalition formation in monetary policy coordination games between n countries. We find that positive spillovers of the coalition formation process and the resulting free-rider problem limit the stable coalition size: since the coalition members are bound by the union's discipline, an outsider can successfully export inflation without fearing that the insiders will try to do the same. In this paper, based on the same model, we allow countries to join competing coalitions. The formation of a large currency bloc is not sustainable since it would impose too much discipline on all participants. However, the co-existence of several smaller currency blocs may be a second-best solution to the free-riding problem of monetary policy coordination.
Keywords: F42; F33; 330; Currency unions; international policy coordination; Free-riding; Coalition formation; Geldpolitik; Internationale wirtschaftspolitische Koordination; Koalition; Währungsunion; Währungsraum; Trittbrettfahrerverhalten; Institutioneller Wettbewerb; Theorie